Kryvorizhzhya and modern children’s literature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article investigates the characteristics of modern children’s literature in Kryvorizhzhya, interpreted and thematic range of the ideological content of works by writers of his native land particular attention is paid to the educational value of the studied works for children.
Keywords: children’s literature; a genre; the ideological content; of the problem